ANALISIS FRAMING PEMBERITAAN KASUS BUNUH DIRI NOVIA WIDYASARI di MEDIA ONLINE - Puji Laksono (Al-Tsiqoh : Jurnal Ekonomi dan Dakwah Islam, 2022)
At the beginning of December 2021, there is a incident that make the public in uproar, that is the suicide case of Novia Widyasari. A student from Sooko District Mojokerto Regency is depressed because of love problems with her boyfriend, Randy Bagus, who is a police officer from the Pasuruan Regency Police. Finally, she suicide at her father’s grave by drinking poison. The case eventually spread throughout the media, the online media Radarmojokerto.id and Beritajatim.com are no exception. Finally, the researcher is interested in researching How is the Framing Analysis of the Suicide Case of Novia Widyasari in Radarmojokerto.id and Beritajatim.com Online Media December 2021 Edition. This study is qualitative research with Robert N. Entman’s framing analysis approach. The object of this research is news about the suicide case of Novia Widyasari in Radarmojokerto.id and Beritajatim.com online media December 2021 edition. To collect data, researchers used the documentation method, that is by copying the news that became the object into one file. The study indicates that the framing analysis of Radarmojokerto.id and Beritajatim.com is different. Starting from Problem Identification, Radarmojokerto.id identified Novia Widyasari’s suicide case as a moral issue, while for Beritajatim.com it was a law issue. Causal Interpretation, according to Radarmojokerto.id, Randy is the perpetrator and Novia is the victim who has suffered a lot, so Novia is highlighted. Meanwhile, according to Beritajatim.com, Randy is the actor causing the problems. Moral Evaluation, Radarmojokerto.id’s moral assessment is focused on Randy as a police officer who is very unfortunate for his actions and also on the community’s sense of empathy for Novia. Meanwhile, according to Beritajatim.com Randy is considered to have embarrassed the institution and his family. The Treatment Recommendation by Radarmojokerto.id is a social movement to express the case of Novia WIdyasari. Meanwhile, Beritajatim.com recommends that Randy as the perpetrator be severely punished.